(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A fishery is an important sector in India. It provides many employments to millions of people and contributes to food security of the country. Introduction of new technology in fishing increased not only the output, but also the cost of production. Production cost plays an important role in deciding fishing operations. This paper analyzed the Growth of production and export of Tamilnadu and Ramanathapuram distrcit. The Researcher used from descriptive analysis for mean, standard deviation, Covariance, Compound Annual Growth Rate (CAGR).